Diagnostic Challenges and Management of Relapsing Polychondritis with Large-Airway Involvement: A Case Series and Literature Review - I-Chun Kuo; Chen-I Hsieh; Yi-Chan Lee; Li-Jen Hsin; Wan-Ni Lin; Michael J. Rutter (Life)
Objectives: Our aim was to investigate the diagnostic challenges and management of relapsing polychondritis (RP) with airway involvement, highlighting the need for accurate diagnosis and effective intervention to prevent severe complications. Methods: In this retrospective study, medical records from January 2011 through June 2024 at a single tertiary-care institution were reviewed. This study was approved by the institutional review board. A total of 34 patients were diagnosed with RP, among whom 4 presented with significant airway complications. This study focused on these four patients, detailing their clinical presentations, diagnostic processes, and outcomes following various interventions. Results: All patients were initially misdiagnosed with asthma and later developed severe airway issues necessitating interventions such as tracheotomy and endotracheal intubation. Diagnostic imaging, microlaryngoscopy and bronchoscopy (MLB) were crucial for identifying subglottic stenosis and other airway alterations. Treatments included high-dose steroids, rituximab, and surgical interventions such as balloon dilation and tracheostomy. Only one patient could be decannulated; the other three remained dependent on tracheostomy and experienced significant complications due to emergency medical interventions. Conclusions: RP can manifest with nonspecific respiratory symptoms similar to asthma, which may delay correct diagnosis and appropriate treatment, leading to critical airway complications. The early, precise identification of RP, particularly with airway involvement, is vital. MLB and dynamic expiratory CT scans play significant roles in clinical diagnosis and management. A multidisciplinary approach involving otolaryngologists, rheumatologists, and pulmonologists is essential for optimizing patient outcomes and minimizing complications.